2011
DOI: 10.1016/j.juro.2010.12.069
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Assisted Laparoscopic Ureteral Reimplantation in Children: Case Matched Comparative Study With Open Surgical Approach

Abstract: Robotic assisted laparoscopic ureteral reimplantation offers similar success rates to the gold standard, open ureteral reimplantation. Future large scale studies will be required to define further the costs and benefits of robotic assisted laparoscopic ureteral reimplantation in the surgical treatment of vesicoureteral reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(94 citation statements)
references
References 17 publications
2
88
1
3
Order By: Relevance
“…As reported previously, the technique is shown to be safe and effective [8,9,12,13,17] . Although the technique remains challenging, robotics certainly add to the precision and ease of most surgical steps when compared to conventional laparoscopy.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As reported previously, the technique is shown to be safe and effective [8,9,12,13,17] . Although the technique remains challenging, robotics certainly add to the precision and ease of most surgical steps when compared to conventional laparoscopy.…”
Section: Discussionsupporting
confidence: 69%
“…Both intra-and extravesical laparoscopic approaches have been described [4][5][6] . This type of surgery can be technically challenging, but since the introduction of robot-assisted laparoscopy especially the extravesical Lich-Gregoir detrusorraphy technique seems a feasible and reasonable treatment option [7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…54 Marchini et al recently reported their outcomes with both intravesical and extravesical robotic-assisted laparoscopic ureteral reimplantation. 55 Compared to case-matched controls consisting of patients who underwent intravesical or extravesical open ureteral reimplantation, there was no difference in either clinically or radiologically defined success, and the robotic approach was associated with reduced bladder spasm, hematuria, catheter duration, and hospital stays. However, in the early phase of this series, the various complications of the robotic approach, ie, postoperative urinary retention and bladder and ureteral leak, led to a higher rate of reintervention.…”
Section: Minimally Invasive Approachesmentioning
confidence: 89%
“…In recent years experiences with RALUR have been accumulated, and various case series have been published. Marchini et al [11] reported lack of any difference among open, and robotic intravesical, and extravesical approaches as for VUR resolution, and operative times. When compared with open surgery, shorter hospital stay, and less frequent vesical spasms were observed in the intravesical robotic group.…”
Section: Discussionmentioning
confidence: 99%